Survei Penggerek Batang Jagung dan Kompleks Musuh Alaminya di Provinsi Gorontalo - Mohamad Lihawa; Witjaksono Witjaksono; Nugroho Susetya Putra (Jurnal Perlindungan Tanaman Indonesia, 2010)
Corn borer is one of the important pests on corn plant in Gorontalo Province, especially in three districts which are the center of maize planting development. Corn borer and its natural enemy complex in Gorontalo Province has not been clearly studied. The purpose of this study is to determine the complexity of the natural enemies of maize stem borer by calculating the diversity and composition. The survey method was used, in which the older larvae, pupae, and corn borer natural enemies were collected from the field in the three districts (Gorontalo, Boalemo, and Pohuwato). Observation plots in each district area of 2,500 m2, were divided into 3 sub plots with the size of 3×3 m, each plot is consisted of 45 plants at the spacing of 75×25 cm. The data were analysed descriptively and organized into tables. Shannon Index was used to count the diversity and composition of the pests and their natural enemies. The results showed that the corn borer species was Ostrinia furnacalis, while the dominant natural enemy was the tachinid fly. The analysis of Shannon diversity index for natural enemies of three districts of Gorontalo, Boalemo, and Pohuwato were 0.63, 0.61, and 0.97 respectively.